Exploring the Community Perspectives on Promoting Inclusion in Performing Arts for Learners with Special Educational Needs: A Preliminary Study - Suhaila Mohamad (International Inclusion Development and Cooperation, 2023)
This preliminary study aims to explore the perspectives towards inclusion in performing arts programs for learners with Special Educational Needs (SEN), identify the barriers and challenges they faced in accessing and participating in performing arts program in the community, identify best practices for promoting inclusion and to develop strategies and recommendations for making performing arts programs more inclusive and accessible in the Malaysian context. Triangulation method was utilised to ensure the validity and reliability of the data collected from 82 participants, namely from online survey, individual interviews, focus group discussions (FGDs) and document analysis. Qualitative methods were employed to analyse the data and gain insights into the attitudes and perceptions of the community towards inclusion in the performing arts programs. Although the findings revealed that most of the community members believe that learners with SEN are adequately supported, there are still significant barriers to inclusion, such as lack of programs and resources, lack of awareness and understanding of the potential of learners of SEN. This preliminary study also provides unique perspectives on the challenges and opportunities for inclusive practices that can consequently contribute to advancing the field of study in special education.